Three Pass Protocol for Key Security Using Affine Cipher Algortima and Exclusive-or (Xor) Combination - Harahap, Muhammad Ikhwan; Suherman, Suherman; Sembiring, Rahmat W (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Information is a very important concern in today's technological era, especially in terms of security through the exchange of information that is so fast that people can easily get various kinds of information. Information obtained easily through recording or openly disseminating data, XOR Cipher is an algorithm used to secure messages and texts but has weaknesses due to simple computation, therefore to strengthen security in XOR Cipher communication protocols can be added to secure key exchange on XOR Ciphers. Affine Cipher can be combined with Exclusive-OR (XOR) for text message security. Through the Affine Cipher algorithm with Key can change the unknown Plaintext, so that the Plaintext is kept secret. The Exclusive-OR (XOR) combination by changing each Character in each Plaintext according to the ASCII Code table can shorten the Key encoding process, so that Plaintext remains safe to send. The Affine Cipher Algorithm and the Exclusive-OR (XOR) Combination for Plaintext security levels are better because the Plaintext encryption and decryption processes are carried out twice with different cryptographic algorithms.